(untitled) (Research, Society and Development, 2024)
Grafting by borbulhia carried out through CATI technology provide rapid production of seedlings and formation of the vineyard, reducing in about a year the start of production. However, there has been an uneven sprouting of the buds and initial development of the seedlings. The objective of this study was to evaluate the effect of the use of auxin AIB associated with brushing of the buds of seedlings with hydrogenated cyanamide (CH) on the uniformity of sprouting and development of grafted seedlings of vine cultivar ’Niágara Rosada’. For were used vine seedlings of uniform diameter of the rootstock ’IAC 766’, grafted with the variety ’Niágara Rosada’, by the borbulhia method. The experimental design was completely randomized, with 10 treatments, 8 repetitions, being 1 (one) seedling per experimental unit, totaling 8 seedlings per treatment, and the averages were grouped by the Scott-Knott test at 5% probability. The following parameters were evaluated: percentage of shoot (%), stem length (cm) and stem diameter (cm). There was a significant difference between the treatments for the evaluated parameters. It was found that the application of CH in the buds, during the first week after planting the seedlings, increases the speed of sprouting of the seedlings and that auxin AIB, applied as a root of the seedlings at the concentration of 1000 ppm for 5 seconds, promotes greater growth and diameter of the stems. It was also found that the use of CH, used in the first week after planting grafted seedlings, with AIB provides seedlings with greater growth and stem diameter.